Umstrittene Sammlungen - Vom Umgang mit kolonialem Erbe aus Kamerun in ethnologischen Museen Die Fälle Tange/Schiffschnabel und Ngonnso'/Schalenträgerfigur in Deutschland und Kamerun - Splettstößer, Anne (Universitätsverlag Göttingen, 2019)
How is the handling of contested "objects" from the German colonial era shaped in ethnological Museums in Germany and Cameroon? This ethnographic study connects, for the first time, approaches from ethnology, (international) law, (art) history and museology which constitute the multidisciplinary field of "return" to deal with this question. Two current return claims of things from Cameroon at ethnological museums in Munich and Berlin take centre stage: Tange/Schiffschnabel and Ngonnso'/Schalenträgerfigur. The reconstruction of the cultural biographies of the contested items documents their part as points of intersection in complex networks of relations and stakeholders from the 19th century to this day. These networks connect people and institutions in Cameroon and Germany and their diverse conceptions and claims on these things in a versatile manner. Return claims, according to the thesis, appear as a magnifying lens which discloses diverging conceptions of things and ontologies.